(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The research note outlines an alternative proof of the equivalence of the Dershowitz-Manna ordering and the Huet-Oppen ordering which was originally presented by Jouannaud and Lescanne. First, some algebraic foundations of multiset orderings are laid which directly or indirectly leads to the result obtained by means of the Huet-Open ordering.